2021
DOI: 10.3390/polym13040616
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Interference Shielding and Physical-Mechanical Characteristics of Rubber Composites Filled with Manganese-Zinc Ferrite and Carbon Black

Abstract: In the present work, composite materials were prepared by incorporation of manganese-zinc ferrite, carbon black and combination of ferrite and carbon black into acrylonitrile-butadiene rubber (NBR). For cross-linking of composites, standard sulfur-based curing system was applied. The main goal was to investigate the influence of the fillers on the physical-mechanical properties of composites. Then, the electromagnetic absorption shielding ability was investigated in the frequency range 1 MHz–3 GHz. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
(23 reference statements)
1
20
0
Order By: Relevance
“…The widespread use of electronic and wireless devices, such as mobile phones, computers, TVs, and radio produces interference from electromagnetic (EM) waves, which affects the performance of these devices in terms of speed and secrecy, loss of data storage and their function, etc. 1–13 Such an exponential increase in EMI could adversely affect human health and lead to many diseases such as leukemia, miscarriages, brain cancer, and could even cause death in some cases. Fig.…”
Section: General Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The widespread use of electronic and wireless devices, such as mobile phones, computers, TVs, and radio produces interference from electromagnetic (EM) waves, which affects the performance of these devices in terms of speed and secrecy, loss of data storage and their function, etc. 1–13 Such an exponential increase in EMI could adversely affect human health and lead to many diseases such as leukemia, miscarriages, brain cancer, and could even cause death in some cases. Fig.…”
Section: General Introductionmentioning
confidence: 99%
“…The earlier review articles have selectively highlighted the EMI shielding and absorption performance of wood-based composites, 4 MXenes, 5,6 rubber composites filled with ferrite and carbon black, 7 carbon nanostructures, 8,9 ultrathin graphene, 10,11 graphene-based composites, 12 carbon nanotube-polymer nanocomposites, 13 polymer nanocomposites, 14–17 porous materials, 18 conducting polymer nanocomposites, 19 core–shell materials, 20 and assembled nano microarchitectures. 21 However, there is still the need for an extensive review article by researchers in this field, covering the performance of carbonaceous, magnetic, and dielectric materials and their nanocomposites and polymer nanocomposites, which includes the importance of the core–shell and the morphology and their past and present trends with updated information in a single window.…”
Section: General Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 In contrast, composite materials mixed with conductive llers in resin materials have become a research hotspot in recent years due to their advantages of being lightweight and having good exibility, corrosion resistance, and good mechanical properties. [6][7][8] In particular, studies have reported various nanocarbon materials as functional llers, such as carbon black (CB), 9,10 carbon nanotubes (CNTs), [11][12][13] graphene nanoplates (GNPs) [14][15][16][17] and vapour-grown carbon bres (VGCFs). 18 Due to their lamellar shape and high-aspect-ratio structure, GNPs are suitable for EMI shielding materials in applications requiring good conductivity.…”
Section: Introductionmentioning
confidence: 99%